Safeguarding Nigerian Youths from Cybercrime: Exploring the Challenges and Potential Solutions - Adam, Usman Ahmed; Mohammed, Munir Abubakar; Mohammed, Hassan Ibrahim (Kashere Journal of Politics and International Relations, 2025)
It remains an undeniable fact that the rapid growth of internet and digital technology has transformed the way Nigerians live, work and interact. However, this digital revolution has also introduces new challenges, particularly among the youths. It is on this background that this paper is set to critically identify and examine ways of safeguarding Nigerian youths from the menace of cybercrime by examining the challenges of mitigating cybercrime among Nigerian youths and prospering potential solutions. To achieve this, Human Needs Theory propounded by John Burton and his associates was used. The study employed content analysis to x-ray the existing documented literatures. The findings show that a dialectical relationship exists between economic crises and youths’ involvement in cybercrime. The relationship is however negative symbiosis where economic crises disempowers and incapacitates the Nigerian youths from meeting their basic needs hence they resort to criminal activities such as phishing, hacking, cracking, cyber stalking among others. The paper also found that although there are regulatory agencies on the ground to curtail the menaces of cybercrime, the performance of such agencies leaves much to be desired. The paper therefore concludes that unless governmental policies and actions are consciously geared towards the achievement of effective, transparent and accountable leadership that will in turn guarantee good governance, safeguarding Nigerian youths from cybercrime will continue to be a mirage. The paper recommends concerted efforts should be made to promote good governance thereby providing job opportunities and improved leaving standard of Nigerians in general and the youths in particular.